A mineral composition of gold-bearing quartz-sericite metasomatites of Ozernoe and Kutyn deposits (Khabarovsk krai) of low-sulphide gold-quartz type - M. Yu. Malykh (Известия высших учебных заведений: Геология и разведка, 2015)
Today we have a huge problem with prospecting new gold-ore deposits and its estimation on deep horizonts, especially in the closed territory. Often we used “analogy” method to make a decision. On that method, we find well known deposit with same type of metallizing process and estimate mineralization of new deposits. Author considered the types of ore-control metasomatite, ore material composition, on the difference deposits of the Khabarovsk Krai: Kutyn and Ozernoe. Irrespective of differences on the deposit geology and geological structure, we can see some common characteristics of ore hosting metasomitite and material composition of gold ores. Basing on those facts we confirm, that Rutin and Ozernoe ore deposits appertain to the same low-sulphide ore formation.